Management of Scout Extracurricular Activities in Junior High School 22 Padang - Ziltri Mila; Alim Harun Pamungkas (Universitas Negeri Padang, 2020)
This research was motivated by the successful achievement of scout extracurricular activities in Junior High School 22 Padang in the last three years. This is suspected because the management of extracurricular activities carried out by the school is getting better done. This study aims to describe the management of scout extracurricular activities in Junior High School 22 Padang. The activities carried out are planning, organizing, actuating, and controlling. This type of research uses descriptive qualitative methods. Sources of data in this study are the principal, vice-principal, supervisor, coach, teacher, and students. Data collection techniques used are the method of observation, interviews, and documentation. Qualitative data analysis used is data reduction, data presentation, and conclusion collection. The data validity technique used is the triangulation technique. Research results obtained, namely: (1) planning to discuss activities, objectives of the formulation, strategies, resources, standards of success, work programs, schedule of activities and sources of funds; (2) organizing include activities, the existence of organizational structure, facilities, and infrastructure, assignment of tasks, recruitment of participants; (3) mobilizing discussion of activities, implementation, and motivation; (4) supervision of issuing activities, evaluating results, solving problems and weak reporting systems.Keywords: Management, Extracurricular, Scout